2016
DOI: 10.1080/09638288.2016.1264012
|View full text |Cite
|
Sign up to set email alerts
|

Experiences of using information and communication technology within the first year after stroke – a grounded theory study

Abstract: People with stroke had a strong drive to integrate ICT in order to manage and bring meaning to their everyday lives, although sometimes they needed support and adaptations. It is not only possible but also necessary to start using ICT in rehabilitation in order to support people's recovery and promote participation in everyday life after stroke. Implications for rehabilitation People with stroke have a strong drive for using information and communication technology in their everyday lives, although support and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
51
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 34 publications
(64 citation statements)
references
References 31 publications
5
51
0
1
Order By: Relevance
“…In Study III, the experiences of using mobile phones after a stroke were explored. General categories were found, and there were some categories in agreement with other qualitative studies (126), but some new characteristics were also discovered. The knowledge from…”
Section: Generalizability Of Findings From the Studiessupporting
confidence: 86%
See 1 more Smart Citation
“…In Study III, the experiences of using mobile phones after a stroke were explored. General categories were found, and there were some categories in agreement with other qualitative studies (126), but some new characteristics were also discovered. The knowledge from…”
Section: Generalizability Of Findings From the Studiessupporting
confidence: 86%
“…Stroke often leads to limitations in interaction, and the mobile phone seemed to have reconnected people with stroke back to the social world. This is also described in a study from Sweden (126), where family and friends kept in touch more frequently through phone calls and text messages after the stroke. The possibility of maintaining a constant connection with friends and relatives was facilitated by mobile phones, which in turn improved their sense of belonging (123).…”
Section: Mobile Phones As a Tool To Facilitate Rehabilitationmentioning
confidence: 85%
“…For instance, White et al [16] described how, among persons with stroke, the use of a tablet was experienced as contributing to motivation, socialization, and was non-burdensome. This is also in line with earlier research showing that people after a stroke were using smartphones and tablets in their everyday life [17,18]. Moreover, smartphones and tablets have been widely integrated in the performance of everyday activities [19,20].…”
Section: Introductionsupporting
confidence: 90%
“…Additionally, digitalization of healthcare is needed in order for the society to manage the challenges of the future with an aging population, lack of healthcare staff and increased demands for accessibility [10]. Our previous study that explored the use of ICT among people after a stroke showed that ICT was used in everyday life, for example to feel safe, staying connected with friends and family and managing daily life [20]. Using a web platform for documentation that is accessible to everyone could enable professionals to make goals and plans more transparent for all stakeholders.…”
Section: Discussionmentioning
confidence: 99%
“…According to the MRC's guidelines, the creation of evidence together with identifying the evidence base are key elements of the development before new, complex interventions can be modeled, tested and eventually implemented [19]. As part of the development of theory, a previous study was performed which showed that people 6-12 months after a stroke had the drive and need to use ICT in their everyday lives, despite having physical and cognitive impairments resulting from the stroke [20]. Another previous study within the research group showed that occupational therapists and people after a stroke emphasized the importance of "sharing and transparency" during the rehabilitation process in order to facilitate a person-centred approach [21,22].…”
Section: Introductionmentioning
confidence: 99%